The Relationship Of Limb Muscle Strength In Smash Badminton In Pb Kepahiang - Ahmad Herianto; Juwita Juwita; Feby Elra Perdima (Sinar Sport Journal, 2021)
The purpose of this study was to determine the relationship between leg muscle strength and smash skills of PB Kepahiang athletes, Bengkulu Province. The method used in this research is correlational quantitative method. The population in this study were athletes from PB Kepahiang, Bengkulu Province, Badminton Sports, totaling 22 athletes, while the sample in this study was 22 athletes. The instrument in this study was a leg muscle strength test and a smash test. Prerequisites of data analysis used were normality test with Lilliefors and homogeneity test. Analysis of the data used is the Product Moment Correlation analysis with a significance level of 5%. Based on the results of the study, it was found that there was a significant relationship between leg muscle strength (X) on the results of badminton smash skills as indicated by rxy = 0.84> r(0.05)(22) = 0.423.